2014
DOI: 10.3171/2014.1.jns131592
|View full text |Cite
|
Sign up to set email alerts
|

Chronic unlimited recording electrocorticography–guided resective epilepsy surgery: technology-enabled enhanced fidelity in seizure focus localization with improved surgical efficacy

Abstract: Object Epilepsy surgery is at the cusp of a transformation due to the convergence of advancements in multiple technologies. Emerging neuromodulatory therapies offer the promise of functionally correcting neural instability and obviating the need for resective or ablative surgery in select cases. Chronic implanted neurological monitoring technology, delivered as part of a neuromodulatory therapeutic device or as a stand-alone monitoring system, offers the potential to monitor patients chronically in their norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…This conclusion is supported by the work of DiLorenzo et al, who found that a group of patients who were poorly localized during acute implantation were well localized after chronic implantation of a neuromodulatory device and developed seizure freedom following resection of their chronically localized network. It is also possible that the emergence of other seizure patterns after months of chronic electrode implantation could be due to secondary epileptogenesis, although data from King‐Stephens, DiLorenzo, and significant relapse rates after resection of well‐localized unilateral temporal lobe seizure during acute intracranial recordings argue against this conclusion . The recurrence of early seizure types later in our canine recordings suggests that the initial seizure types are likely not a transient result of tissue reaction postimplantation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This conclusion is supported by the work of DiLorenzo et al, who found that a group of patients who were poorly localized during acute implantation were well localized after chronic implantation of a neuromodulatory device and developed seizure freedom following resection of their chronically localized network. It is also possible that the emergence of other seizure patterns after months of chronic electrode implantation could be due to secondary epileptogenesis, although data from King‐Stephens, DiLorenzo, and significant relapse rates after resection of well‐localized unilateral temporal lobe seizure during acute intracranial recordings argue against this conclusion . The recurrence of early seizure types later in our canine recordings suggests that the initial seizure types are likely not a transient result of tissue reaction postimplantation.…”
Section: Discussionmentioning
confidence: 65%
“…One recent study analyzing 82 patients who were implanted chronically with the NeuroPace Responsive Neurostimulator System (RNS) demonstrates that an accurate representation of the spatial and temporal variability of seizures in these patients requires at least 30 days of continuous monitoring . Another study demonstrates that this prolonged monitoring may reveal patients to have well‐localized seizures and be good surgical candidates, although this was not apparent during the standard inpatient iEEG monitoring period …”
mentioning
confidence: 99%
“…Seizure onset localization relies on identifying subtle electrographic changes that are spatially distinct, so any changes in spatial variability may interfere with the localization procedure. Of interest, there is evidence that patients who appear to have multifocal onset seizures immediately after electrode implantation during standard clinical evaluation localize to one predominant area in the chronic steady state, eventually resulting in seizure-free outcome after surgery 45 . This provides at least circumstantial evidence that the chronic steady state may better reflect a patient’s baseline than alterations of the network from implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have highlighted the diagnostic power of the RNS System, using chronic ECoG recorded by the device to characterize longitudinal dynamics of epileptiform activity (DiLorenzo et al, 2014; King-Stephens et al, 2015; Mackow et al, 2016; Smart et al, 2013). Here, we extend the research applications of the RNS System by recording fine-grained physiological responses from eloquent cortex over long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…The neurostimulator detects abnormal patterns of activity and responds by delivering brief, imperceptible pulses of electrical current to inhibit seizure activity. Although the RNS System is a clinical tool, the availability of chronic ECoG in ambulatory patients offers an unprecedented opportunity to study longitudinal patterns of brain activity (Anderson et al, 2015; DiLorenzo et al, 2014; King-Stephens et al, 2015; Smart et al, 2013; Spencer et al, 2016). However, the ability of the RNS System to record physiological responses from eloquent cortical regions has not been reported.…”
Section: Introductionmentioning
confidence: 99%